THE LABOUR MARKET IN UKRAINE: CURRENT CHALLENGES (Economic journal of Lesya Ukrainka Volyn National University, 2020)
The effective functioning of the labour market in Ukraine depends, first of all, on the social and economic situation in the country, structural changes in the wourld and national economies are influencing. Globalization, increased competition, development of knowledge economy and information technologies, restructuring of the economy, accelerated economic growth, scientific and technological progress, informatization of society and state regulation have significant impact on the labour market. Long-term imperfection in the interaction between the labour market and the educational market has had a negative effect on both of them, causing the discrepancy between qualification standards and the requirements of the national economy, worsening the quality of staff training and aggravating the disbalance between labour supply and labour demand. This led to a decrease in labour productivity and competitiveness of domestic enterprises, the existence of part-time and unreported employment, the increase of structural and technological unemployment and the inability to provide innovative economic development. Structural changes in the world and national economies influence the formation of aggregate demand in the labour market for qualified specialists who have high level of intellectual potential and will be able to combine several professions. To overcome educational and qualification disbalance between the educational and labour markets, it is necessary to update educational standards and curricula, to apply new teaching methods and training techniques, to improve the mechanism of interaction between both markets. The employees who have unique competencies and are capable of creating innovative technologies and solutions will be in advantageous positions. Scientific and technological progress causes mass automation, robotization, computerization, digitization and, consequently, changes the employment structure significantly, thus posing serious challenges for the labour and educational markets. In a competitive environment, higher and vocational education should be flexible and focus on the future needs of the economy. State regulation of the labour market is an important area of development of the national economy and a necessary process, since it directly affects the expansion of employment opportunities, improving the welfare and living standards of the population. In the market economy environment the labour market should: provide the working population with the income which meets their social and economic needs; reduce social inequality in society and ensure social and economic stability; make the most of the country's labour potential.
Keywords: labour market, educational market, employment, unemployment, demand, supply, labour, state regulation.